Latitudinal decrease in folivory within Nothofagus pumilio forests: dual effect of climate on insect density and leaf traits? - Garibaldi, Lucas Alejandro (2010)
Fil: Garibaldi, Lucas Alejandro. Universidad Nacional del Comahue. Centro Regional Universitario Bariloche; Argentina